Plant Autophagy: An Intricate Process Controlled by Various Signaling Pathways - Wang, Pingping; Wang, Tongtong; Han, Jingyi; Li, Ming; Zhao, Yanxiu; Su, Tong; Ma, Changle (Frontiers in Plant Science, 2021)
Autophagy is a ubiquitous process used widely across plants cells to degrade cellular material and is an important regulator of plant growth and various environmental stress responses in plants. The initiation and dynamics of autophagy in plant cells are precisely controlled according to the developmental stage of the plant and changes in the environment, which are transduced into intracellular signaling pathways. These signaling pathways often regulate autophagy by mediating TOR (Target of Rapamycin) kinase activity, an important regulator of autophagy initiation; however, some also act via TOR-independent pathways. Under nutrient starvation, TOR activity is suppressed through glucose or ROS (reactive oxygen species) signaling, thereby promoting the initiation of autophagy. Under stresses, autophagy can be regulated by the regulatory networks connecting stresses, ROS and plant hormones, and in turn, autophagy regulates ROS levels and hormone signaling. This review focuses on the latest research progress in the mechanism of different external signals regulating autophagy.